2021
DOI: 10.1371/journal.pone.0259528
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between happiness and quality of life: A model for Spanish society

Abstract: A key goal for society as a whole is the pursuit of well-being, which leads to the happiness of its individual members; as such, it is of critical socioeconomic relevance. In this regard, it is important to study which factors primarily affect the happiness of the population. In principle, these factors are associated with income level and residential and job stability, or more specifically, citizens’ quality of life. This research, which is based on a multidimensional concept of quality of life, uses a regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
1
11
0
7
Order By: Relevance
“…We thus quantify this relationship or coefficient γ for each factor analysed ( Table 1 ). The mathematical relationship follows a linear formulation, as supported by the analyses conducted by López-Ruiz et al [ 40 ] on citizen happiness, according to the equation where α is the independent term and ɛ is a random variable with zero expectation, uncorrelated and with constant variance. The measures of goodness of fit for the explanation of variance by the k factors can be checked through the adjusted coefficient of determination R 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We thus quantify this relationship or coefficient γ for each factor analysed ( Table 1 ). The mathematical relationship follows a linear formulation, as supported by the analyses conducted by López-Ruiz et al [ 40 ] on citizen happiness, according to the equation where α is the independent term and ɛ is a random variable with zero expectation, uncorrelated and with constant variance. The measures of goodness of fit for the explanation of variance by the k factors can be checked through the adjusted coefficient of determination R 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Kim (2019) in a study examined the mediating effect of optimism on the relationship of middle school students' stress and happiness at school and indicated that enhancing optimism is an effective strategy for improving the happiness at school. Some studies have also addressed the role of family environment on adolescent happiness (López-Ruiz, Huete-Alcocer, Alfaro-Navarro, & Nevado-Peña, 2021;Nes, Czajkowski, & Tambs, 2010). Fararouei, Brown, Toori, Haghighi, and Jafari (2013) indicated that happiness was associated with lower BMI, regular physical activity, absence of exposure to second-hand smoke, higher consumption of fruits and vegetables, and spending leisure time with family.…”
Section: Ieepjmentioning
confidence: 99%
“…People make efforts to fulfill various needs such as happiness and success throughout their lives. Given that human life is finite, achieving happiness is critical for increasing the quality of life (Javanmardnejad et al, 2021; López‐Ruiz et al, 2021). Individual, social, and environmental factors may influence the efforts to achieve happiness.…”
Section: Introductionmentioning
confidence: 99%